Values education curriculum for high school student in Vietnam: A brieft overview. - Nguyen , Thi Nhu Quynh (Universiti Sains Malaysia, 2014)
Currently, there have been no separate values education subject taught in Vietnam educational settings. The values are normally integrated with other science majors and instructed as moral education at primary school, citizenship education and out-of-class activities at secondary and high school.